Interfacial chemistry of rocks and soils - Nagy, Noemi M. (Surfactant science series, 2010)
"Knowledge of the basic interactions that take place between geological materials and different substances is the first step in understanding the effects of adsorption and other interfacial processes on the quality of rocks and soils, and on driving these processes towards a beneficial or neutral result. Interfacial Chemistry of Rocks and Soils examines the different processes at solid and liquid interfaces of soil and rock, presenting a complete analysis that emphasizes the importance of chemical species on these interactions"--Jacket.